ANALISIS DAMPAK EKONOMI PENAMBANGAN EMAS ILEGAL MENURUT KONSEP EKONOMI PEMBANGUNAN BERKELANJUTAN DAN MAQASHID SYARIAH: STUDI KASUS KECAMATAN BATANG NATAL KABUPATEN MANDAILING NATAL - Yusuf Siregar, Andri; Arif Lubis, Fauzi; Ria Armayani Hasibuan, Reni (Penerbit Lafadz Jaya, 2023)
The aspects of the problem studied by the author are regarding the economic impact of illegal gold mining according to the economic concept of sustainable development and maqashid sharia. The aim of this research was to determine the economic impact of illegal gold mining according to the economic concept of sustainable development and maqashid sharia. The analysis technique used is descriptive qualitative research methods. Qualitative methods are research procedures that produce descriptive data in the form of written or spoken words from people or observable behavior. Descriptive research is a research method that describes all the data or conditions of the research subject or object, then analyzed and compared based on the current reality and then tries to provide a solution to the problem and can provide up-to-date information so that it is useful for the development of science and more can be applied to a variety of problems. The results of the research show that this illegal gold mining produces results very quickly compared to previous work, namely farming and other things, and the results obtained are very promising and able to fulfill the family economy, people who take part in mining activities can earn Rp. 600,000-Rp. 800,000 per the week. Mining may be carried out as long as the community considers the interests of the public good, does not cause damage and is environmentally friendly. The community has the perception that the existence of illegal gold mines in Batang Natal District brings benefits and increases the welfare of the local community because the existence of the Unlicensed Gold Mining (PETI) location has become a new job opportunity for people who do not have permanent jobs. The positive impact felt by the surrounding community is of course the creation of new jobs for miners. The negative impact of gold mining which is felt almost every day by the community around the mining area is water pollution.